Effects of magnesium niobate precursor and calcination condition on phase formation and morphology of lead magnesium niobate powders - Wongmaneerung R. (2014)
A perovskite phase of lead magnesium niobate, Pb(Mg1/3Nb2/3)O3 or PMN, powders has been synthesized by a rapid vibro-milling technique. Both columbite MgNb2O6 and corundum Mg4Nb2O9 have been employed as magnesium niobate precursors, with the formation of the PMN phase investigated as a function of calcination conditions by thermal gravimetric and differential thermal analysis (TG-DTA) and X-ray diffraction (XRD). The particle size distribution of the calcined powders was determined by laser diffraction technique. Morphology, crystal structure and phase composition have been determined via a combination of scanning electron microscopy (SEM), transmission electron microscopy (TEM) and energy-dispersive X-ray (EDX) techniques. The magnesium niobate precursor and calcination condition have been found to have a pronounced effect on the phase and morphology evolution of the calcined PMN powders. It is seen that optimisation of calcination conditions can lead to a single-phase PMN in both methods. However, the formation temperature and dwell time for single-phase PMN powders were lower for the synthetic method employing a columbite MgNb2O6 precursor. © 2006 Elsevier B.V. All rights reserved.